Gene therapy in cardiomyopathies - Review of the latest reports - Magdalena Strzelczyk; Gabriela Pabis; Joanna Wziątek; Paula Bętkowska; Iwona Koziołek; Piotr Kowalik; Patrycja Fatyga; Wiktoria Fatyga; Daria Krzyżanowska; Kinga Dowierciał (Quality in Sport)
Introduction and purpose